2016
DOI: 10.1016/j.stem.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Activation of NF-κB in BRCA1-Deficient Mammary Progenitors Drives Aberrant Proliferation and Accumulation of DNA Damage

Abstract: Human BRCA1 mutation carriers and BRCA1-deficient mouse mammary glands contain an abnormal population of mammary luminal progenitors that can form 3D colonies in a hormone-independent manner. The intrinsic cellular regulatory defect in these presumptive breast cancer precursors is not known. We have discovered that nuclear factor kappaB (NF-κB) (p52/RelB) is persistently activated in a subset of BRCA1-deficient mammary luminal progenitors. Hormone-independent luminal progenitor colony formation required NF-κB,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 57 publications
4
92
0
1
Order By: Relevance
“…Linking BRCA1’s roles in proper mammary cell differentiation and DSB repair, recent studies have shed light on why luminal progenitor cells may be more sensitive to defects in BRCA1’s DSB repair function (Nolan et al 2016, Sau et al 2016). Luminal progenitors in preneoplastic breast tissue from BRCA1 mutation carriers separate into two distinct populations, RANK+ and RANK−, based on expression of the receptor for RANK ligand, a paracrine effector of progesterone signaling.…”
Section: Tissue Tropism Of Brca-mutated Cancers and Cell Of Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Linking BRCA1’s roles in proper mammary cell differentiation and DSB repair, recent studies have shed light on why luminal progenitor cells may be more sensitive to defects in BRCA1’s DSB repair function (Nolan et al 2016, Sau et al 2016). Luminal progenitors in preneoplastic breast tissue from BRCA1 mutation carriers separate into two distinct populations, RANK+ and RANK−, based on expression of the receptor for RANK ligand, a paracrine effector of progesterone signaling.…”
Section: Tissue Tropism Of Brca-mutated Cancers and Cell Of Originmentioning
confidence: 99%
“…Combined with the observation that the RANK+ cells have a molecular signature more similar to basal-like breast cancer than any other subtype, these findings suggest that the RANK+ luminal progenitor cells may represent the cell-of-origin population for the basal-like breast cancers arising in BRCA1 mutation carriers and that RANK ligand (RANKL) may be a valuable therapeutic target in these patients (Nolan et al 2016). Similarly, the NF-κB pathway is persistently activated in a subset of luminal progenitor cells from preneoplastic BRCA1 mut /+ breast tissue (Sau et al 2016). Sau et al (2016) found that progesterone-stimulated proliferation increases NF-κB signaling and the accumulation of DNA damage.…”
Section: Tissue Tropism Of Brca-mutated Cancers and Cell Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these authors also found a significant RANKL-dependent reduction of tumour incidence in a mouse model of transplanted mammary tumours [71]. Moreover, in another study, nuclear factor kappaB (NFκB), a well-known downstream target of RANK, was shown to be persistently activated by DNA damage in BRCA1 -deficient mammary progenitors and in vivo inhibition of NFκB prevented hormone-independent colony formation of luminal progenitor cells [72]. Figure 4 depicts the current understanding of RANKL/RANKL function in BRCA1 -mutated breast cancer.…”
Section: Rank and Rankl Link Female Sex Hormones To Brca1 Mutation-inmentioning
confidence: 99%
“…Genome-wide comparative analyses of multiple transgenic mammary tumor models have suggested PyMT + model to represent the luminal B intrinsic subtype of breast cancer (21). We used dimethylaminoparthenolide (DMAPT), a water-soluble analogue of parthenolide, which we have previously shown to have potent NF-κB inhibitory activity (22) and has been shown to overcome the adverse effects of persistent activation of NF-κB in BRCA1-deficient mammary luminal progenitor cells in vivo (23). We found that mammary tumor development in PyMT + mice was accompanied with functional limitations such as reduced grip strength, impaired rotarod balance, causing altered body composition as well as molecular changes in muscle including reduced expression of miR-486 and MyoD as we reported previously (14).…”
Section: Introductionmentioning
confidence: 99%